Análisis de la prescripción de marca y de la identificación de su naturaleza publicitaria por parte de rostros televisivos en Instagram - Dra. Araceli CASTELLÓ-MARTÍNEZ,Dr. Jesús SEGARRA-SAAVEDRA,Dra. Tatiana HIDALGO-MARÍ (Fonseca, Journal of Communication, 2023)
Despite its expansion, the Internet continues to be a medium that receives low legislative attention, in which professional practice is ahead of the regulatory standard. Social networks, in general, and Instagram, in particular, are used as a channel in which to monetize the prescribing power of relevant people in the digital field by taking advantage of these legal loopholes